Dysregulated Phenylalanine Catabolism Plays a Key Role in the Trajectory of Cardiac Aging. Issue 7 (17th August 2021) - Czibik, Gabor; Mezdari, Zaineb; Murat Altintas, Dogus; Bréhat, Juliette; Pini, Maria; d'Humières, Thomas; Delmont, Thaïs; Radu, Costin; Breau, Marielle; Liang, Hao; Martel, Cecile; Abatan, Azania; et al.
Abstract : Background: Aging myocardium undergoes progressive cardiac hypertrophy and interstitial fibrosis with diastolic and systolic dysfunction. Recent metabolomics studies shed light on amino acids in aging. The present study aimed to dissect how aging leads to elevated plasma levels of the essential amino acid phenylalanine and how it may promote age-related cardiac dysfunction. Methods: We studied cardiac structure and function, together with phenylalanine catabolism in wild-type (WT) and p21 −/− mice (male; 2–24 months), with the latter known to be protected from cellular senescence. To explore phenylalanine's effects on cellular senescence and ectopic phenylalanine catabolism, we treated cardiomyocytes (primary adult rat or human AC-16) with phenylalanine. To establish a role for phenylalanine in driving cardiac aging, WT male mice were treated twice a day with phenylalanine (200 mg/kg) for a month. We also treated aged WT mice with tetrahydrobiopterin (10 mg/kg), the essential cofactor for the phenylalanine-degrading enzyme PAH (phenylalanine hydroxylase), or restricted dietary phenylalanine intake. The impact of senescence on hepatic phenylalanine catabolism was explored in vitro in AML12 hepatocytes treated with Nutlin3a (a p53 activator), with or without p21-targeting small interfering RNA or tetrahydrobiopterin, with quantification of PAH and tyrosine levels. Results: Natural aging is associated with a progressive increase in plasma phenylalanine levels concomitant with cardiac dysfunction, whereas p21 deletion delayed these changes. Phenylalanine treatment induced premature cardiac deterioration in young WT mice, strikingly akin to that occurring with aging, while triggering cellular senescence, redox, and epigenetic changes. Pharmacological restoration of phenylalanine catabolism with tetrahydrobiopterin administration or dietary phenylalanine restriction abrogated the rise in plasma phenylalanine and reversed cardiac senescent alterations in aged WT mice. Observations from aged mice and human samples implicated age-related decline in hepatic phenylalanine catabolism as a key driver of elevated plasma phenylalanine levels and showed increased myocardial PAH-mediated phenylalanine catabolism, a novel signature of cardiac aging. Conclusions: Our findings establish a pathogenic role for increased phenylalanine levels in cardiac aging, linking plasma phenylalanine levels to cardiac senescence via dysregulated phenylalanine catabolism along a hepatic-cardiac axis. They highlight phenylalanine/PAH modulation as a potential therapeutic strategy for age-associated cardiac impairment. Abstract : Supplemental Digital Content is available in the text.